Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1464-410x.2012.10960.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oncological outcomes after segmental ureterectomy or radical nephroureterectomy in urothelial carcinomas of the upper urinary tract: results from a large French multicentre study

Abstract: Study Type – Therapy (multi‐centre retrospective cohort) Level of Evidence 2b What's known on the subject? and What does the study add? Upper urinary tract urothelial carcinomas (UUT‐UCs) are rare tumours. Because of the aggressive pattern of UC, radical nephroureterectomy (RNU) with bladder cuff removal remains the ‘gold‐standard’ treatment. However, conservative strategies, such as segmental ureterectomy (SU) or endourological management, have also been developed in patients with imperative indications. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 27 publications
(37 reference statements)
4
78
0
2
Order By: Relevance
“…Recent publications have reported a 9% to 11% ipsilateral recurrence rate Outcomes of segmental/total ureterectomy in UTUc in patients undergoing segmental resection. 13,20,21 Our series of patients (SU and TU) demonstrated an 11.1% ipsilateral upper tract recurrence rate, commensurate with prior literature (Fig. 1).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Recent publications have reported a 9% to 11% ipsilateral recurrence rate Outcomes of segmental/total ureterectomy in UTUc in patients undergoing segmental resection. 13,20,21 Our series of patients (SU and TU) demonstrated an 11.1% ipsilateral upper tract recurrence rate, commensurate with prior literature (Fig. 1).…”
Section: Discussionsupporting
confidence: 73%
“…18,19 Colin and colleagues, in the largest published study, evaluated 52 distal SU patients and 416 NU patients, demonstrating similar 5-year DSS (87.9% vs. 86.3%, p = 0.99). 20 Jedres and colleagues performed a Surveillance, Epidemiology, and End Results (SEER)-database review of 569 SU and 1222 NU patients and described similar oncologic outcomes between groups (5-year DSS 86.6% vs. 82.2%, p = 0.05). 21 Our 3-year DSS and OS for the ureterectomy group (SU and TU) was 69.7% and 54.9% compared to 69.2% and 56.3% for the NU group (p = 0.78 and p = 0.80, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study compared survival outcome after segmental ureterectomy versus radical NU in TCC of ureter. Short-term oncological outcomes were similar and they concluded that segmental ureterectomy should be considered an option (Colin et al, 2012). We performed conservative surgery in 2 patients and they are follow-up without recurrences.…”
Section: Discussionmentioning
confidence: 71%
“…In patients with isolated ureteral cancers, there is evidence to suggest equivalent outcomes with segmental ureterectomy compared to nephroureterectomy (7,8) although radical nephroureterectomy with bladder cuff removal remains the gold standard for patients with upper tract urothelial cancers (9). Patients with incomplete nephroureterectomy are at increased risk for bladder cancer and potentially decreased survival.…”
Section: Discussionmentioning
confidence: 99%